2008
DOI: 10.1007/s00436-008-1296-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the essential oils of Lippia turbinata and Lippia polystachya (Verbenaceae) on the temporal pattern of locomotion of the mosquito Culex quinquefasciatus (Diptera: Culicidae) larvae

Abstract: The essential oils (EO) of Lippia turbinata (TUR) and Lippia polystachya (POL) have shown lethal effects against mosquito larvae. The present work evaluated whether these EO at doses ranging from sublethal to lethal (20, 40 and 80 ppm) modify the temporal pattern of locomotion of Culex quinquefasciatus larvae. Larvae were individually placed in glass boxes, and their activity recorded at 0.3 s intervals during 40 min. Individuals treated with doses >40 ppm of either EO significantly decreased their ambulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…In this context, DFA has emerged as an effective tool to measure the temporal organizational complexity of animal behavior [15,16], due mainly to the facts that it could be applied to non stationary time series and because it is able to eliminate trends in data. For example, DFA has been found useful to detect subtle changes in behavioral patterns due to sublethal doses of the toxic compound [17], or stressful events [18][19][20] that could go undetected by conventional behavioral analyses which are often limited to measures of the mean duration or frequency of particular behaviors [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, DFA has emerged as an effective tool to measure the temporal organizational complexity of animal behavior [15,16], due mainly to the facts that it could be applied to non stationary time series and because it is able to eliminate trends in data. For example, DFA has been found useful to detect subtle changes in behavioral patterns due to sublethal doses of the toxic compound [17], or stressful events [18][19][20] that could go undetected by conventional behavioral analyses which are often limited to measures of the mean duration or frequency of particular behaviors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Fractal analyses, to the extent to which they have been applied in this context, can thus enhance our understanding of behavioural variation and how it relates to stress and disease (Rutherford et al 2004;Asher et al 2009). Indeed, various studies have demonstrated cases in which fractal analyses were able to detect behavioural consequences of various stressors whereas traditional, frequency-based approaches were not (Motohashi et al 1993;Alados et al 1996;Rutherford et al 2004;Rutherford et al 2006;Kembro et al 2009a;Kembro et al 2009b). Rutherford et al (2004) therefore stress that fractal analysis can be a useful tool in behavioral assessments of animal welfare because of its ability to objectively measure qualitative differences in temporal sequences.…”
Section: Complexity Loss and Animal Behaviormentioning
confidence: 99%
“…The optimal complexity range, which we might think of as an attractor like those found in SOC, would first need to be identified in order to determine when and whether complexity loss has taken place. This might be done via comparisons of free-ranging individuals in various physiological conditions or exposed to various environmental stressors (Alados et al 1996;Alados & Huffman 2000;MacIntosh et al 2011;Seuront & Cribb 2011) or through direct manipulation of the system to bring forth desired outcomes (Alados & Weber 1999;Rutherford et al 2003;Maria et al 2004;Seuront et al 2004b;Kembro et al 2008;Kembro et al 2009a;Seuront 2011;Cottin et al 2014). As always, the key challenges concern eliminating confounding factors and natural variability in the first case (observational) and assuming natural behavior as a starting point under unnatural conditions in the second (experimental).…”
Section: Complexity Loss Revisited: the Bigger Picturementioning
confidence: 99%
See 1 more Smart Citation
“…and Lippia polystachya Griseb. reportedly demonstrated lethal effects against mosquito larvae of Culex quinquefasciatus, where ambulation speed and total time of ambulation was significantly decreased (Kembro et al, 2009). Essential oil of Lippia sidoides Cham.…”
Section: Introductionmentioning
confidence: 99%